2016
DOI: 10.1103/physrevc.93.014909
|View full text |Cite
|
Sign up to set email alerts
|

Linear and cubic response to the initial eccentricity in heavy-ion collisions

Abstract: We study the relation between elliptic flow, v2 and the initial eccentricity, ε2, in heavy-ion collisions, using hydrodynamic simulations. Significant deviations from linear eccentricity scaling are seen in more peripheral collisions. We identify the mechanism responsible for these deviations as a cubic response, which we argue is a generic property of the hydrodynamic response to the initial density profile. The cubic response increases elliptic flow fluctuations, thereby improving agreement of initial condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 69 publications
12
114
0
Order By: Relevance
“…In particular, k 2 is expected to be ≤ 0.15 in the centrality range 0-60% [81]. The residual differences in α, ε 0 and k 2 when including k 2 as an additional free parameter are considered in the systematic uncertainties.…”
Section: Jhep07(2018)103mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, k 2 is expected to be ≤ 0.15 in the centrality range 0-60% [81]. The residual differences in α, ε 0 and k 2 when including k 2 as an additional free parameter are considered in the systematic uncertainties.…”
Section: Jhep07(2018)103mentioning
confidence: 99%
“…This coefficient is introduced to quantify the possible increase of flow fluctuations that the hydrodynamic expansion of the medium introduces with respect to geometrical fluctuations in the initial state and was argued to be non-zero in mid-central and peripheral collisions due to general properties of the hydrodynamic phase [81]. In particular, k 2 is expected to be ≤ 0.15 in the centrality range 0-60% [81].…”
Section: Jhep07(2018)103mentioning
confidence: 99%
“…Theoretical calculations have shown that for elliptic and triangular flows (n = 2, 3), the magnitudes of the anisotropic flow coefficients v n are approximately linear in the magnitude of the initial eccentricity coefficients arXiv:1602.02813v2 [nucl-th] 30 Mar 2016 n , except for large impact parameters [5][6][7][8][9]. Since shear viscosity reduces the hydrodynamic response v n to the initial eccentricity n , v n / n for n = 2, 3 was proposed in [5,10] as a clean observable to quantitatively constrain the shear viscosity of quark-gluon plasma.…”
Section: Introductionmentioning
confidence: 99%
“…It is now understood [54] that the initial spatial anisotropies present in the early stages of nucleus-nucleus collisions are converted to final stage momentum anisotropies (i.e., anisotropic flow) in a way that is consistent with viscous relativistic hydrodynamic simulations performed on an event-by-event basis (see, e.g., the review [47]). Furthermore, once the full information regarding the soft event-by-event v n distributions became available [55] at the LHC, powerful constraints on the initial conditions of the hydrodynamic modeling of the QGP have been obtained [56][57][58][59][60]. Nevertheless, these recent advances regarding event-by-event medium fluctuations have not yet been incorporated in theoretical studies of high p T observables.…”
mentioning
confidence: 99%